2016
DOI: 10.3109/2000656x.2015.1137927
|View full text |Cite
|
Sign up to set email alerts
|

Distal anastomosis patterns of the descending branch of the lateral circumflex femoral artery

Abstract: The reverse ALT flap technique showed good results in the treatment of patients with skin and soft tissue defects around the knee and shin. Variations of the anastomoses and branching patterns of the db-LCFA may influence flap survival. Additional preoperative vascular evaluations would be helpful in defining the most compatible area from which to harvest the flap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 10 publications
1
13
1
Order By: Relevance
“…The typical pattern for DAT occurs when it branches off the LCFA, which in turn branches off the PFA. This was observed in 62.75% of limbs in the present study; these results align with the majority of previous studies that have found this pattern to be present in 74%-82% of limbs analyzed (Pan et al 2004;Boonrod et al 2016).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The typical pattern for DAT occurs when it branches off the LCFA, which in turn branches off the PFA. This was observed in 62.75% of limbs in the present study; these results align with the majority of previous studies that have found this pattern to be present in 74%-82% of limbs analyzed (Pan et al 2004;Boonrod et al 2016).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, a study from Taiwan of 11 limbs found this typical branching pattern in 82% of limbs (Pan et al 2004). Similarly, a study from Thailand of 50 limbs observed the typical branching pattern in 80% of dissected limbs (Boonrod et al 2016), while a Japanese study of 70 limbs reported the typical branching pattern in 74% of the limbs studied (Kimata et al 1998). An angiogram review study conducted in Thailand analyzing 194 lower limbs also observed this pattern in 79% of limbs (Burusapat et al 2016).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The SLGA subdivides into an anterior (also named superficial or patellar) and a posterior (also named deep or condylar) branch, and is responsible for the blood supply to the lateral femoral condyle, the lateral head of the gastrocnemius muscle, the vastus lateralis muscle and the biceps femoris muscle (Kirschner ). Furthermore, the iliotibial tract and the overlying skin at the superolateral side of the knee are supplied by the SGLA (Laitung, 1989;Hayashi & Maruyama, 1990b;Zhang, 1990;Pan et al 2004;Fathi et al 2008;Pan & Taylor, 2009;Nguyen et al 2011;Boonrod et al 2016;Parvizi et al 2016;Morsy et al 2018). Apart from the DGA, the SLGA was the artery most often identified in this study.…”
Section: Slgamentioning
confidence: 57%
“…Information on the morphology of the artery may be frequently found (Walton & Bunkis, 1984;Hayashi & Maruyama, 1990b;Kirschner et al 1998;Wong et al 2015;Morsy et al 2018). Also the supplied profound structures and the location of the respective skin areas were described (Laitung, 1989;Hayashi & Maruyama, 1990b;Zhang, 1990;Pan et al 2004;Fathi et al 2008;Pan & Taylor, 2009;Nguyen et al 2011;Boonrod et al 2016;Parvizi et al 2016;Morsy et al 2018), but data on the respective size of the perforator angiosomes are hitherto lacking.…”
Section: Introductionmentioning
confidence: 99%